The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1080/13540602.2010.517682
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling as dialogue: how teachers construct professional knowledge

Abstract: This study shows how a group of English language lecturers use storytelling as a form of professional dialogue. The aim of the study is to highlight the dialogic role of storytelling in supporting the construction of lecturers' professional knowledge and not to identify lecturers' professional knowledge. In a professional development project, 12 lecturers created digital stories about their experiences of professional development. These stories were shared with colleagues who then responded with their own digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…This idea represents a view of narrative as a dialogue and challenges the notion of history as individual construction. Savvidou (2010) points out that if we observe the everyday social interactions, we find that the fact of telling a story of personal experience is not presented as a monologue, but as part of an interactional event, a conversation in which stories are mutually constructed by participants. In this process, including the roles of the storyteller and recipient are interchangeable.…”
Section: Digital Stories In Corporative Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea represents a view of narrative as a dialogue and challenges the notion of history as individual construction. Savvidou (2010) points out that if we observe the everyday social interactions, we find that the fact of telling a story of personal experience is not presented as a monologue, but as part of an interactional event, a conversation in which stories are mutually constructed by participants. In this process, including the roles of the storyteller and recipient are interchangeable.…”
Section: Digital Stories In Corporative Trainingmentioning
confidence: 99%
“…Here, we also want to emphasize the concept of narrative of Savvidou (2010), for whom the idea of storytelling is inherently dialogical, so whenever a story is told, it causes a response. That is, the stories we tell are shaped by the answers of real or potential interlocutors.…”
Section: Digital Stories In Corporative Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Para este autor el sentido se produce y circula a través del lenguaje que es polifónico por definición ya que materializa un conjunto de voces que provienen de distintos orígenes, tiempos, culturas y contextos sociales inscritos al interior de éste. En cambio, la tendencia en el campo investigativo de los docentes se ha focalizado en el relato de sus experiencias desde una perspectiva de naturaleza más bien monológica, representada principalmente en una voz: el relato de su historia como profesor (Savvidou, 2010). Por ende, falta el desarrollo de estudios de narrativas de profesores desde una perspectiva dialógica, que incorporen a través del análisis de sus discursos, no sólo la voz del docente formador entendida como el resultado de un proceso de formación y desarrollo profesional, sino como la construcción y re-significación constante del tejido discursivo que incorpora, a través diversos mecanismos de relación, las voces internamente convincentes de personas e instituciones que han incidido e inciden en este proceso.…”
Section: Introductionunclassified
“…In addition, storytelling activities in the learning process have an important role in the development of students psychologically through the disclosure of motivation and character of the story being revealed (Nguyen, Stanley, Stanley, & Wang, 2015;Frude & Killick, 2011). Storytelling is seen as a way for teachers to implement their knowledge and understanding in the world of education (Savvidou, 2010). In fact, several studies have revealed that storytelling can have a positive impact on improving students' ability to communicate, which is seen in the mastery of vocabulary and understanding story content (Caminotti & Gray, 2012;Zare et al 2016).…”
mentioning
confidence: 99%